Upaya Guru Meningkatkan Partisipasi Siswa Tunarungu Melalui Adaptasi Bahasa Oral di SLB-B Karya Murni Medan - Nurmayani Nurmayani; Nurcahaya Lumban Gaol; Oni Catrine Joana Simbolon; Tiana Silalahi; Ulyanti Pandiangan (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This research provides an in-depth analysis of the various efforts made by teachers at SLB Karya Murni B Medan to increase deaf students' active participation through the implementation of spoken language adaptation measures. The researcher adopted a descriptive qualitative approach to collect data through a series of direct observations, in-depth interviews, and comprehensive notes to describe the learning process and the dynamics of teacher-student interaction. The research findings show that teachers have implemented various spoken language adaptation strategies in a consistent and structured manner, supported by close collaboration with families and provision of adequate facilities. However, educators still face many key challenges, such as the different abilities of individual students and the limitations of learning media, which need to be addressed systematically. The implementation of oral adaptation is proven to have a significant impact on increasing students' active engagement in the learning process, not only academically but also in terms of their socio-emotional development. This study makes an important contribution to the development of inclusive education and provides concrete recommendations to improve the quality of learning for deaf students in Indonesia.